Latihan Interval Meningkatkan Kapasitas Kardiorespirasi Pada Atlet Remaja - Rahmiwati, Rahmiwati; Syah, Irhas (Universitas Fort De Kock Bukittinggi, 2020)
AbstractVO2max is an indication of a person's cardiorespiratory endurance. There are various factors that affect the VO2max value, one of which is physical exercise. Some examples of physical exercise, namely interval training, are one way to measure the VO2max value. Knowing the effect of interval training on VO2max in arema club soccer athletes in the Sijunjung district, Sijunjung district. This type of research is quasi-experimental. The research sample was the arema club nagari siaur football athlete, Sijunjung district (n = 10) whose VO2max was measured using the Balke Test method. The normality test is Mann-Whitney. The mean VO2max value of the interval training group was Mean 51.2 ml / kg / minute with a minimum value of 50.5 ml / kg / minute and a maximum value of 52.2 ml / kg / minute. Provision of interval training is very beneficial and also has an effect on increasing vo2max in football athletes Arema Club Sijunjung district. Physiologically, it can improve the cardiovascular condition of the ball players. Keywords : Kardiorespirasi, Interval Exercise